Using Big Data Analytics for Decision Making: Analyzing Customer Behavior using Association Rule Mining in a Gold, Silver, and Precious Metal Trading Company in Indonesia - Yudhistyra , Wecka Imam; Risal , Evri Marta; Raungratanaamporn , I-soon; Ratanavaraha , Vatanavongs (International Journal of Data Science, 2020)
Indonesia is facing many challenges in the fourth industrial revolution (4IR) era. One of them is related to big data technologies and implementation that can be seen clearly from Indonesia Industry Readiness Index (INI) 4.0. Therefore, focusing on implementing big data analytics in a gold, silver, and precious metal trading company is the objective of this manuscript to support daily business operations. To be more specific, the aim is to discover meaningful patterns and ensure high quality of knowledge discovery from the big data available in a company in Indonesia. It is needed to support the Making Indonesia 4.0 as a roadmap to implement industrial digitalization in Indonesia. The methodology used for the big data implementation in this manuscript is the combination of the CRISP-DM framework and key steps for customer analytics. The result of this research is a list of recommendations that facilitate strategic planning based on evidence of measurable big data analytics to achieve the business goals of a company.